GAMBARAN TINGKAT KEPUASAN PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN TENTANG PELAYANAN ADMINISTRASI KEPESERTAAN DI BPJS KESEHATAN KANTOR CABANG UTAMA (KCU) BANDUNG: An Overview of the Satisfaction Level of Health Participants of BPJS on Membership Administration Service at the Health BPJS Main Branch Office of Bandung - Mutiafani Hanafi (JURNAL TERAS KESEHATAN, 2019)
This study is motivated by the improving number of participant and it must be coupledwith the increasing quality of service rendered by service providers. Many insurancecompanies demand the insurance provider to improve the quality of service. Theproblem in this research is the presence of some complaints from participants of theadministrative service in Badan Penyelenggara Jaminan Sosial (BPJS) KesehatanKantor Utama (KCU) Bandung, one of the problems is the waiting time is too long inthe place of making the cards. The method used in this research is descriptive method. Collection of data use a sheet of an interview, by giving of an interview to the 30respondent who comes to BPJS. Measuring the level of participant satisfaction bycomparing expectation and reality by using five dimensions ; tangible, reliability, responsiveness, empathy and assurance. Based on the result of research conducted,,the level of participant satisfaction BPJS are as follows : dimension of tangible 76,5%, dimension of reliability 68 %, dimensions of responsiveness 71 %, dimension ofempathy 76 % and dimension of assurance 69 %, As a whole the dimension ofsatisfaction level participants attain average 72,1 % lay on the Satisfied level.